2014
DOI: 10.1128/cvi.00200-14
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the Trivalent Inactivated Influenza Vaccine in Young Children Less than 4 Years of Age, with a Focus on Age and Baseline Antibodies

Abstract: fIn this study, we assessed the effects of the prevaccination titer and age on the immunogenicity of a low dose of influenza vaccine in children less than 4 years of age. A total of 259 children received two vaccine doses (0.1 ml for 0-year-olds and 0.2 ml for children 1 year of age or older) 4 weeks apart during the 2005/2006 season. The hemagglutination inhibition antibody titers were measured before vaccination and 4 weeks after the first and second doses. The geometric mean titer, mean fold rise, serorespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…Compared with the VE among adults or in older children, the modest VE we observed may be reflective of lower immunogenicity of non-adjuvanted inactivated influenza vaccines in young children [5] , [23] , [24] , [25] , [26] , [27] . Phase II immunogenicity studies have shown that young children 6–11 months have lower geometric mean antibody titers and lower rates of seroprotection than older children [5] , [23] , [25] , [28] , [29] .…”
Section: Discussionmentioning
confidence: 59%
“…Compared with the VE among adults or in older children, the modest VE we observed may be reflective of lower immunogenicity of non-adjuvanted inactivated influenza vaccines in young children [5] , [23] , [24] , [25] , [26] , [27] . Phase II immunogenicity studies have shown that young children 6–11 months have lower geometric mean antibody titers and lower rates of seroprotection than older children [5] , [23] , [25] , [28] , [29] .…”
Section: Discussionmentioning
confidence: 59%
“…We previously reported that younger age was a predictor of lower immunogenicity of IIV independent of baseline antibody titer level, as a result of a study of Japanese children aged 6 months to 3 years in the 2005/2006 season. [ 17 ] Since the dosage of IIV used in the 2005/2006 study was below the current standard, especially for 0-year-olds (0.1 mL/dose vs 0.25 mL/dose), the possibility remains that the lower response at the younger age was due to the low dosage. This interpretation of the result had been consistent with a previous study in Japanese children.…”
Section: Discussionmentioning
confidence: 99%
“…Lower vaccine responses in elderly people Humoral responses aP: GMTs (52,53) HepB: SPRs (55) OPV: SPRs (15) Diphtheria: SPRs (16) OPV: SPRs (15) Tetanus: SPRs (16) wP: SPRs (16) Diphtheria: SPRs (60) HepA: GMTs (61,63,65,142), SCRs (63,76), SPRs (61,62,65,142) HepB: GMTs (61,69,71,73,75,77), SCRs (70,71,75,80,110), SPRs (61, 62, 66-69, 72-75, 77-79, 81) PPV23: GMTs (82-84) TBE: GMTs (88) Tetanus: GMTs (88), SPRs (60,89) TIV: GMTs (87) Cellular responses BCG: Th1, Th2, Treg responses (18) BCG: CD4 T cell response (17) TIV: Th cell and cytotoxic T cell responses (86), lymphoproliferative responses (87) Cytokine responses BCG: IL-6 and IL-17 production (18) TIV: IL-2 (85), IL-10 (87), and IFN-␥ (87) production age than in younger children (93), and GMTs after meningococcal conjugate vaccine (MCV-C) vaccination are higher in children over the age of 10 years than in younger children …”
Section: Lower Vaccine Responses In Neonates and Young Infantsmentioning
confidence: 99%
“…Individuals with higher prevaccination tetanus antibody titers have higher SPRs after booster vaccination (60), while the antibody response to diphtheria is not affected by prevaccination titers (391). Similarly, the antibody response to TIV is positively associated with prevaccination titers (93). Elderly people who have low antibody titers against influenza virus before vaccination might not seroconvert after one dose of TIV (392).…”
Section: Vaccination or On B Or T Cell Responses (341) To Tiv Vaccinamentioning
confidence: 99%